Low pathotype diversity in a recombinant Puccinia striiformis population through convergent selection at the eastern Himalayan centre of diversity (Nepal). (20th December 2017) - Ali, S.; Sharma, S.; Leconte, M.; Shah, S. J. A.; Duveiller, E.; Enjalbert, J.; de Vallavieille‐Pope, C.
Abstract : Worldwide Puccinia striiformis f. sp. tritici (Pst) epidemics have been reported to be driven by few genetic lineages, while a high diversity is evident at the Pst Himalayan centre of diversity. This study investigated the relationship between pathotype diversity and genetic structure in Nepal, the eastern Himalayan region, which has been largely unexplored. Despite the high genetic diversity and recombinant structure detected through microsatellite genotyping, characterization of virulence phenotypes for 62 isolates identified only eight pathotypes, with two pathotypes predominant over all the populations. This is in contrast to the Pakistani and Chinese recombinant populations, where high pathotype diversity is associated with genetic diversity. The most prevalent Nepali pathotype was not a unique clonal lineage, but was represented by seven multilocus genotypes from four distinct genetic subgroups, suggesting strong directional selection on virulence genes, resulting in convergent pathotypes in distinct genetic groups. This convergent selection is discussed in comparison with clonal French and recombinant Pakistani populations. Additionally, the Nepali Pst population carried virulence to 17 out of 24 tested yellow rust resistance genes ( Yr ), with the absence of virulence to Victo and Early Premium and resistance genes Yr5, Yr10, Yr15, Yr24 and Yr26 . Virulence to Yr2, Yr7, Yr27 and YrSu were fixed in all isolates, in line with the deployment of these resistance genes in Nepal. The results reflect the influence of resistance gene deployment on selection of virulence and pathotypes in a recombinant pathogen population, which must be considered in the context of durable resistance gene deployment.